Apology of Subjectivity, in Science and Social Relations (Global Journal of Human-Social Science, 2023)
A subjectivity is the confessed manifestation of a created social coexistence, or interrelation of individuals that is socially integrated to reproduce and produce its development possibilities; production that is represented by a subject, a phenomenon commonly known eventually as "subjectivity", which is nothing more than the "social representation" of a "construction" through an individual who represents an active "social integration", or "intersubjectivity"."; therefore: "subjectivity" is not a simple opinion as an isolated definition of an individual, it is rather a manifest "intersubjectivity", or represented by a subject of a social unit in interaction; being that this, as a created social manifestation, is an ideal reproduction of conditions of a developing coexistence that has built as a process "subjects" that manifest the experiences produced as part of a "social integration" or "intersubjectivity" that is created, o constantly produced as definitions of reproduction and social development; Hence, a subjective manifestation is a represented intersubjectivity, that is, a subject as a social individual, only "is", insofar as, a "state" to "be" from its manifestation, or represented social interrelation that allows it to "be" and "transcend" as a representative of a collectivity; Hence, "subjectivity" is the demonstrative graphic representation of a community, from a "collective construction" to which it represents, or applies through an individual; manifestation that reproduces, variable and complex, -depending on the different types of coexistence-matrices of social development to prevent and act in their social interaction with others; which means defining subjectivity as a created social product, where a subject represents a plurality of interrelations produced and in production, a process that this article will deal with as part of a hermeneutic methodical relationship that pretends, or rather presumes, to understand such interrelationship.
Keywords: subjectivity; subject; intersubjectivity; experience; science; representation; interaction; consciousness; being